When I dream of heaven : Angelina's story - Kroll, Steven (Jamestown's American portraits, 2000)
In 1895 in New York City, Gina, a fourteen-year-old Italian immigrant, forced by her family to drop out of school and work long hours in a garment factory, tries to break free of the control her parents have over her finances and social life.